2007
DOI: 10.1074/jbc.m611473200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Atg3, an Autophagy-related Ubiquitin Carrier Protein (E2) Enzyme that Mediates Atg8 Lipidation

Abstract: Atg3 is an E2-like enzyme that catalyzes the conjugation of Atg8 and phosphatidylethanolamine (PE). The Atg8-PE conjugate is essential for autophagy, which is the bulk degradation process of cytoplasmic components by the vacuolar/lysosomal system. We report here the crystal structure of Saccharomyces cerevisiae Atg3 at 2.5-Å resolution. Atg3 has an ␣/␤-fold, and its core region is topologically similar to canonical E2 enzymes. Atg3 has two regions inserted in the core region, one of which consists of ϳ80 resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
157
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(170 citation statements)
references
References 32 publications
2
157
1
Order By: Relevance
“…Furthermore the cleavage of Atg3 by calpain 1 in the region separating the domains that interact with Atg7 and Atg8 may result in uncoordinated conjugate formation and inefficient autophagy induction. 36 This site is also conserved in the mouse and rat. Further study will be required to ascertain whether Atg3 cleavage has any cellular relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the cleavage of Atg3 by calpain 1 in the region separating the domains that interact with Atg7 and Atg8 may result in uncoordinated conjugate formation and inefficient autophagy induction. 36 This site is also conserved in the mouse and rat. Further study will be required to ascertain whether Atg3 cleavage has any cellular relevance.…”
Section: Discussionmentioning
confidence: 99%
“…35 The cleavage sites of caspase-3, -6 or -8 in Atg3 are predicted to fall in the region that is required for its interaction with Atg7, 36 ( Table 1) and are conserved in the mouse and rat. Atg7 and Atg3 are the E1 and E2 enzymes respectively that catalyse the lipidation of Atg8 (LC3, GATE-16 or GABARAP).…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that a GFP tag at either terminus of Atg3 yielded a non-functional protein that would be inappropriate for use in this study. Therefore, we screened for permissive sites for GFP insertion, referring to structural information obtained previously for S. cerevisiae Atg3 (20). In particular, we evaluated three GFP insertion sites C-terminal to the handle region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GFP tagging at the N terminus might obstruct the interaction of this domain with PE, resulting in functional impairment (32). Although it is not clear whether the C-terminal domain of Atg3 has an interaction partner, this domain is located very close to the E2-like domain of Atg3 (20). In the Atg3⅐Atg7 complex, the flexible region of Atg3 is rearranged to interact with a distal groove in the N-terminal domain of Atg7 (33).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of Atg3 shows a hammer-like conformation with an N-terminal head moiety and a Cterminal handle moiety [161]. The head moiety shares some similarities to canonical E2 enzymes, while the handle moiety, which is suggested to bind Atg7, is unique to Atg3.…”
Section: Two Ubl Protein Conjugation Systemsmentioning
confidence: 99%